Study the Role of Social Capital in Urban Instauration of old Contexture Case Study: Jooybar City - Dr. Alireza khajeh shahkohi khajeh shahkohi; Masoud Modanlou Joybari; Reza Samadi (جغرافیا و آمایش شهری منطقه‌ای, 2013)
Urban instauration is one of thoughtful plans in confronting with depreciation of old contextures, which in view of merely physiced has some similar results with the other urban development plans. On this basis, social capital with comprising values including trust, partnership and solidarity in residential areas, is a concept which has found a special importance in Urban Instauration process in the recent decades. The purpose of this study is to investigate the relationship between social capital  with  the physiced interventions model and the incentive to continue the residing on one hand and the  type and amount of relationship between social capital with participation increase and the rate in executing urban renewal plans , the research method is descriptive- analytical which is based on surveying strategy. The obtained data and information were gathered through questionnaires between 143 families residing at Joybar Kord Mahale and were analyzed by chi-squared tests and Pearson correlation coefficient and chi( two sided). The obtained results showed that physiced interventions in living environments  is for the  promotion of social capital of the habitats which this relation  with chi-squared amount of 63.056 has been confirmed at meaningful level of 99% and also the incentive for continuation of settlement will increase the social capital in the texture which this relation has been confirmed at meaningfull level of 99% by chi-squared amount of 6783. In this direction it is recommended that the primary physical intervention models and motivation strengthening   to be performed in appropriate with the local potentials and requirements. And consequently the promotion of social capital which leads to the participation increase and speed up the work in urban renovation plans.